Subject as an effect of language - Ratajczak, Mikołaj (Hybris, 2015)
The article presents a detailed analysis of language as a dispositive. Drawing a general idea from the writings of Foucault, Deleuze, Agamben and Virno, the project of the linguistic constitution of the subject is developed in distinguishing three levels of the analysis, these levels being also the three modes of the existence of language-dispositive: the sentence, the enunciation and the utterance. According to the idea presented in the article, the analysis of the language-dispositive consists in showing the basic oppositions, on which each level of the existence of the language operates, and how each of these oppositions enables the linguistic constitution of the subject – with these oppositions being: sense/reference, signiefié/signifiant and meaning/showing. The article concludes with the analysis of negation and negativity as the phenomenon introduced into the life of the human animal through language-dispositive. The distinction of the three modes in which language as a dispositive operates enables a complete presentation of how negation can be understood as a function of the process of subjectivization.